Student Perceptions of the Use of ChatGPT in Learning Activities - mukti, dazza; Artika, Salsa; Suendra, Malya; Vitalis, Alvin; Patty, Elyakim Nova Supriyedi (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The development of artificial intelligence (AI) technology, particularly ChatGPT, has transformed the way students obtain information and complete learning assignments. While offering various conveniences, the use of ChatGPT also raises concerns regarding dependence on technology and a decline in critical thinking skills. Therefore, it is important to understand students' perceptions of its use in learning. This study aims to analyze students' perceptions of ChatGPT's use, including aspects of usefulness, ease of use, attitudes toward use, and challenges faced. The study used a descriptive quantitative approach involving 60 students as respondents selected using a purposive sampling technique. Data were collected through a Google Forms-based questionnaire and analyzed using descriptive statistics in the form of percentages and average scores. The results showed that students' perceptions of ChatGPT's use were in the strong category with an average percentage of 62%. Most students considered ChatGPT to help accelerate reference searches, assignment completion, and material understanding. However, the use of ChatGPT also has the potential to cause learning distractions and dependence on instant answers. These findings contribute to enriching studies on the use of AI in learning and provide a basis for educators to design strategies for using ChatGPT that are more thoughtful, critical, and responsible to support the learning process.